Wpływ paranoi politycznej na dyskurs publiczny w Polsce - Jakubowski, Jakub (Wydawnictwo Naukowe WNPiD UAM, Poznań, 2011)
The transition of the polish political system has had a significant influence on the shape of public discourse. Undoubtedly, politicians’ and society members’ disposition to paranoid behavior is the reason of public debate`s exacerbation and deep conflict between conservatives and liberals. The abundance of political changes, breakthrough circumstances and crisis situations in the last few years have fuelled this trend. In fact, the influence of political paranoia on Polish discourse seems to be destabilized and it provokes a question: how to make debate more substantive and rational?

Tranzycja systemu politycznego w Polsce istotnie wpłynęła na kształt publicznego dyskursu. Bez wątpienia dyspozycja zarówno polityków jak i członków społeczeństwa do zachowań paranoicznych stanowi przyczynę zaognienia debaty publicznej oraz głębokiego konfliktu między środowiskami konserwatywnym i liberalnym. Mnogość politycznych zmian, okoliczności czasów przełomu oraz sytuacje kryzysowe w ostatnich kilku latach ugruntowały ten trend. W rezultacie, wpływ paranoi politycznej na polski dyskurs publiczny wydaje się być czynnikiem destabilizującym i skłania do postawienia pytania: w jaki sposób uczynić ową debatę bardziej rzeczową i racjonalną?
The Influence of Political Paranoia on Public Discourse in Poland
Keywords: paranoja; dyskurs; demokracja